Array of water|room temperature ionic liquid micro-interfaces - Silvester, Debbie; Arrigan, Damien (Elsevier, 2011)
Cyclic Voltammetry and AC Voltammetry were used to characterise the micro-interface array between water and a commercially available room temperature ionic liquid (RTIL) trihexyltetradecylphosphonium tris (pentafluoroethyl)trifluorophosphate ([P14,6,6,6][FAP]) for the first time. The interface array was formed within the micropores of a silicon chip membrane (30 pores and 23 m diameter). The polarisable potential window and capacitance curves were recorded, and the transfers of three cations (tetraalkylammoniums) and three anions (tetraphenylborate, hexafluorophosphate and tetrafluoroborate) across the interface were studied. The shapes of the voltammograms revealed that the RTIL filled the pores and that the interface was located at/near the pore mouths. This is the first report of voltammetry at an array of water|RTIL microinterfaces, rather than at a single interface or porous polymer supported-interface. This work is particularly relevant to the sensing/extraction of redox-inactive ions.